On one series of the VI century AD iron one-piece asian helmets - Adam Kubik; Oleg Radyuš; Leonid Vyazov (Banber Arevelagitut'yan Instituti)
The article describes a series of helmets of a type that probably spread across Asia and Eastern Europe in the middle to the second half of the VI century AD. These helmets are characterised by a very particular construction: they have a bowl hammered from a single piece of iron, with an additional band in the lower part, connected to the inside or outside edge of the helmet. Additionally, a chainmail collar was attached to the lower part of the helmet. The attached chainmail provides additional protection around the entire circumference including the forehead above the eyes. This characteristic would remain unpopular in European armaments for quite a long period and was only popularised in central and eastern Europe around the XVI century AD [1: 130]. This article analyses a possible Iranian provenance of the helmets of this type as well as hypothesizes about the possible reason for the spread of these helmets on the territory of Eastern Europe and Asia.